Improving governance learning for sustainable development: introductory reflections on a specific issue in adult education - Giovanna Del Gobbo (Formare, 2019)
Good governance is considered a pillar in the implementation of the Sustainable Development Agenda 2030. Failures in governance processes are considered to be at the origin of countless problems in ecosystem services management. The influence of formal and informal institutions, the role of state and non-state actors, the nature of multi-level interactions and the importance of social and economic conditions, that can facilitate or increase citizen participation, are identified as structural features of governance systems. The functioning of these systems is conceptualized as social learning as a conceptual framework to understand the dynamics and the adaptive capacity of governance systems to develop learning. Informal networks are considered to play a crucial role in these learning processes. This contribution presents a reflection on learning dimension of governance, based on relationships among sustainability, human development and ecosystem protection.